Illicit Drug Use Initiation in the Nordic Countries - Moeller, Kim (International Journal of Criminology and Sociology, 2013)
Abstract: The aim of this review is to provide an overview of the most important research into young people's initiation of illicit drug use in the Nordic countries. A systematic literature review was undertaken in Sweden, Denmark, Norway, combined with a qualified search in Finland and Iceland. The search was based on the PubMed and Sociological Abstracts databases in combination with Google Scholar. A total of 333 documents were reviewed, primarily English peer-reviewed articles, but also reports and books in the Nordic languages. 46 documents were chosen to represent the research into illicit drug initiation in the Nordic countries. The review has two parts. In the first part the typical drug initiation sequence and the different interpretations of this sequence in the Nordic countries is presented. In the second part four categories of risk factors are identified, and a review of the most significant Nordic research into these is presented. The categories are: parenting styles, emotional control, sensation-seeking behaviour, collective identity-creation processes, and risk perceptions.